PERAN HUKUM SEBAGAI PEMBAHARUAN MASYARAKAT MENURUT DANTE - Begouvic, M Eza Helyatha; Wathan, Ferroka Putra; Cuan, Bayu (Bahasa Indonesia, 2022)
Law has always been the foundation of hope for the Indonesian people to bring about justice. Justice which is one of the goals of law should be practiced in an effort to build society, not to try people in development under the pretext that we are a country of laws, the formulation of the problem in this research, namely What is the Role of Law as Community Renewal and What is Dante's Philosopher's View of the Role Law as Community Renewal, the research method uses data originating from the literature, so the results of this study are that Law in Dante's concept is not interpreted as a tool but as a means of community renewal. The main ideas that underlie this concept are that order and regularity in development and renewal efforts are desired, even considered, and that law in the sense of rules is expected to direct human activity in the direction desired by such development and renewal and according to Dante this power is evident in the form organized chart. Power in the form of an organization can be obtained based on religious legitimacy, elite ideological legitimacy, or pragmatic legitimacy based on the highest source of power or sovereignty.